2020
DOI: 10.3390/geosciences10080305
|View full text |Cite
|
Sign up to set email alerts
|

Eurocode 7 and Rock Engineering Design: The Case of Rockfall Protection Barriers

Abstract: The Eurocode 7 or EC7 is the Reference Design Code (RDC) for geotechnical design including rock engineering design within the European Union (EU). Moreover, its principles have also been adopted by several other countries, becoming a key design standard for geotechnical engineering worldwide. It is founded on limit state design (LSD) concepts, and the reliability of design is provided mainly by a semi-probabilistic method based on partial factors. The use of partial factors is currently an advantage, mainly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…As a result, the uncertainties on the geometric properties of discontinuities have to be con sidered by alternative methods, such as sensitivity analyses, in the same way as when no reliabilitybased methods are used, or even using probabilistic descriptions of the discon tinuities and partial factors for the actions and the strengths [24] und Smith und Walter [25]. From a rock engineering perspective, a key challenge for the rock engineer in using calculations may be to define the hazardous ground behaviour as a calculable limit state, as discussed by Vagnon et al [27]. Moreover, concerning the partial factor method specifically, theoretical concerns have been raised regarding its ability to yield consistent safety margins.…”
Section: Comments On Verification Using Calculation For Rock Engineer...mentioning
confidence: 99%
“…As a result, the uncertainties on the geometric properties of discontinuities have to be con sidered by alternative methods, such as sensitivity analyses, in the same way as when no reliabilitybased methods are used, or even using probabilistic descriptions of the discon tinuities and partial factors for the actions and the strengths [24] und Smith und Walter [25]. From a rock engineering perspective, a key challenge for the rock engineer in using calculations may be to define the hazardous ground behaviour as a calculable limit state, as discussed by Vagnon et al [27]. Moreover, concerning the partial factor method specifically, theoretical concerns have been raised regarding its ability to yield consistent safety margins.…”
Section: Comments On Verification Using Calculation For Rock Engineer...mentioning
confidence: 99%
“…As a result, heuristic techniques are usually used in the selection of some inputs. In areas where a fire has occurred, these estimates are no longer valid because of the effect that the fire may have had on the source areas and propagation zone, and hence the changes that may occur in the volume of the rock block and the rockfall trajectories [107][108][109].…”
Section: Degradation and Obsolescence Of Protective Measuresmentioning
confidence: 99%
“…The investigations cover effect of discontinuity persistence, reliability analysis of 3D wedge mechanisms, probabilistic rock slope analysis, Monte Carlo simulations, system reliability involving multiple failure modes, response surface method, distinct element method and random set theory, determination of Coulomb shear strength parameters from the generalized Hoek-Brown criterion, probabilistic analysis using point estimate methods, Barton-Bandis failure criterion, probabilistic characterization of rock mass from limited data, and other worthy issues. In addition, Vagnon et al (2020a) applied FORM and RBD for debris flow barriers and demonstrated the applicability and limitations of EC7 for these rock engineering structures, and Vagnon et al (2020b) investigated the complementarity of the RBD approach within EC7 principles by analyzing the design of a slope subjected to rockfall.…”
Section: Introductionmentioning
confidence: 99%